Integrated Energy System Planning Based on Equipment Performance. Issue 1 (September 2020) - Yang, Yang; Wei, Mengju; Liu, Zhao; Wang, Yongli; Cai, Chengcong; Zhou, Minhan; Song, Fuhao
Abstract: The Integrated Energy System (IES) has the advantage of improving energy utilization and promoting energy flexibility. Its equipment configuration is one of the keys to Integrated Energy System planning. This paper takes equipment selection and capacity planning as the goal establishes the IES equipment selection and capacity planning model makes the minimum annual inclusive cost as the optimization goal and uses the mixed-integer linear programming algorithm to solve the practical problem. Finally, a typical southern park is taken as an example to analyze and verify the feasibility of the model and algorithm.